Ivabradine Enhances its Positive Impact on the Heart Muscle/ (Myocardial Infarction) by Modulating Myocardial Nitric Oxide and ATP-dependent K+ Channels but not by Adenosine and Bradykinin Levels - Tantray, Junaid; Sharma, Ashish Kumar; Sharma, Rajesh Kumar (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: This study aimed to explore the cardioprotective effects of ivabradine and examine potential secondary mechanisms beyond the established role of If-HCN channel inhibition demonstrated in cellular studies. Objectives: Our hypothesis centered on the idea that Ivabradine could induce responses similar to ischemic preconditioning involving nitric oxide, adenosine, bradykinin, and ATP-dependent potassium channels. Materials and Methods: Ischemia-reperfusion injury was established using Langendroff’s technique. 20 min ischemia and 40 min reperfusion to coronary artery to isolated heart was model of myocardial infarction. There were following groups: Control (Ischeamia-Reperfusion), Ischemic preconditioning, ivabradine (10 μmol/L), ivabradine+L-NAME (30 μmol/L) and ivabradine+Aminoguanidine (30 μmol/L), ivabradine+Theophylline (50 μmol/L), ivabradine+Aminophylline (50 μmol/L), ivabradine+Enalapiril (100 μmol/L), ivabradine+Losartan (50 μmol/L), ivabradine+Gliclazide (30 μmol/L), ivabradine+glimepiride (50 μmol/L) in perfusat. Results: Ivabradine has demonstrated the potential for providing cardiovascular defence. (Infarct Size: 5.334±0.422%; LDH: 101.500±1.147 I.U.; CK-MB: 100.167±1.302 I.U.) Ischemic preconditioning presents significant potential for enhancing cardioprotective effects. Infarct Size: 5.1667±0.478% LDH: 101.667±2.789 I.U.; CK-MB: 97.167±1.721 I.U.). Ivabradine+L-NAME (Infarct size: 64.167±0.872%; LDH: 154.667±1.256 I.U.; CK-MB: 200.167±1.537 I.U.). Ivabradine+Aminoguanidine (Infarct Size: 64.500±0.885%; LDH: 154.833±1.138 I.U.; CK-MB: 198.333±1.145 I.U.). Ivabradine+Theophylline (Infarct Size: 5.333±0.422%; LDH: 102.5±2.923 I.U.; CK-MB: 97.167±1.721 I.U.). Ivabradine+Aminophylline (Infarct Size: 5.667±0.333%; LDH: 102.833±1.515 I.U.; CK-MB: 100.833±1.250 I.U.). Ivabradine+Enalapril (Infarct Size: 5.500±0.428%; LDH: 102.667±1.498 I.U.; CK-MB: 100.667±1.429 I.U.). Ivabradine+Losartan (Infarct Size: 5.333±0.667%; LDH: 102.167±1.751 I.U.; CK-MB: 101.833±1.400 I.U.). Ivabradine+Gliclazide (Infarct Size: 63.833±1.352%; LDH: 154.667±1.054 I.U.; CK-MB: 201.833±1.815 I.U.). Ivabradine+Glimepiride (Infarct Size: 63.667±0.989%; LDH: 155.833±1.352 I.U.; CK-MB: 199.833±1.579 I.U.). Conclusion: Ivabradine and ischemic preconditioning exhibited cardioprotective effects by reducing infarct size, along with Lactate Dehydrogenase isoenzyme (LDH) and Creatine Kinase isoenzyme (CK-MB) levels. In contrast, treatments with L-NAME, Aminoguanidine, Gliclazide, and Glimepiride led to increased infarct size, LDH, and CK-MB levels. Meanwhile, Theophylline, Aminophylline, Enalapril, and Losartan contributed to a reduction in infarct size, LDH, and CK-MB levels. These findings suggest that ivabradine-induced cardioprotection does not involve nitric oxide, adenosine, or bradykinin pathways.
Keywords: Cardioprotection; Nitric oxide; KATP channels; Myocardial infarction; Ivabradine; animal models